The Effect of Vitamin D₃ Supplementation on Diarrhea Frequency, Duration, and Neutrophil-to-Lymphocyte Ratio (NLR) in Children with Diarrhea - Wibowo, Satrio; Wulandari, Kirnia Tri; Amalia, Nurlinah (Trends in Immunotherapy, 2026)
Diarrhea remains a major cause of morbidity in children under five, and although current management is mainly supportive, Vitamin D₃ supplementation has emerged as a potential immunomodulatory approach whose clinical efficacy requires further clarification. This study aimed to evaluate the effect of Vitamin D₃ supplementation on clinical outcomes, specifically diarrhea frequency, duration, and neutrophil-to-lymphocyte ratio (NLR) in children with acute diarrhea. This single-blind, randomized controlled trial employed a pre-post test control group design involving 34 pediatric patients with diarrhea. Participants were allocated into two groups: one receiving standard therapy alone (control) and the other receiving standard therapy plus oral Vitamin D₃ supplementation for 14 days. Outcome measures included diarrhea frequency, duration, and neutrophil-to-lymphocyte ratio (NLR), evaluated pre-post intervention. Post-intervention analysis showed significant improvements in the intervention group compared to controls: shortened diarrhea duration (p = 0.002), reduced diarrhea frequency (p = 0.000), but no significant with NLR reduction (p = 0.124); however, the median delta NLR decreased more in the Vitamin D₃ group (−2.57) than in the control group (−0.13) (p = 0.031). No significant differences in dehydration status were observed between groups (p = 1.000). The intervention group also exhibited a marked increase in serum 25(OH)D levels post-supplementation (p = 0.000). However, after adjusting for baseline NLR using ANCOVA, the reduction was no longer directly attributable to the intervention (p = 0.09), though a strong trend favoring the Vitamin D group persisted. Vitamin D₃ supplementation may serve as an adjunctive immunotherapy, as it demonstrated beneficial effects on clinical outcomes in pediatric diarrhea, suggesting its potential through anti-inflammatory and immunomodulatory properties.